HUBUNGAN PENGETAHUAN, PERSEPSI, DAN DUKUNGAN SUAMI TERHADAP MINAT MELAKUKAN IMUNISASI DASAR LENGKAP PADA BAYI DI WILAYAH KERJA PUSKESMAS SILAT HILIR KALIMANTAN BARAT TAHUN 2023 - Tika, Lionarda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In 2019, the achievement indicator for the percentage of children aged 0-11 months who received complete basic immunization was 82.9%, (below the National target of 93%), this year's achievement increased compared to the achievement in the past 3 years, this is in line with the 2019 target. This study aims to determine the relationship between knowledge, perception and support from husbands on interest in carrying out complete basic immunization for babies in the Silat Hilir Health Center working area, West Kalimantan in 2023. Using analytical descriptive with a cross sectional approach. The population used in this research were mothers who had babies in the Silat Hilir Health Center working area, West Kalimantan. The sampling technique involved a total sampling of 87 mothers of babies. The results of the research show that there is a relationship between knowledge (P-value 0.000), perception (P-value 0.000), and husband's support (P-value 0.000) on interest in carrying out complete basic immunization for babies in the Silat Hilir Health Center working area, West Kalimantan in 2023. Conclusion there is a relationship between knowledge, perception and husband's support for interest in carrying out complete basic immunization for babies in the Silat Hilir Health Center working area, West Kalimantan in 2023. Suggestions for mothers of babies to be able to increase their knowledge and understanding of the benefits and importance of providing complete basic immunization to babies, So it is hoped that this increase in knowledge can change bad perceptions into good ones and increase immunization coverage for babies